IDENTIFIKASI SECARA CEPAT BAHAN BIOAKTIF PADA TUMNUHAN DI LAPANGAN - Chairul Chairul (BERITA BIOLOGI, 2003)
New drug discovery from natural products (bio-prospecting) is not an easy works and takes time, big budget, human resources etc. some important approaches must be taken in order to get success. A preliminary observation of biologycally active components is impotant approach in order that more selective in collecting research materials in the field. This approach is purposed to pacilitate (make easier) the next step research process later in the laboratory level. Several Methods of preliminary observaton of biologyvcally active components had been carried out in the field, but the general guideline of fast observation had been used e.g. 1). Etno-botany (Etnomedicine and Etnopharmacology), 2). Chemotaxonomy, 3). Organoleptic, 4). Chemical (reagent kit) and 5).Simple bioassay in the field (fish posion test, insecticide). Besides that collecting the herbarium specimen as well as research materials for any scienfitic and laboratory works. This paper described these approaches in order to make useful methods to researchers, who go to the field and they could collect more selective research materials before bring them to laboratory.